Research in the social scientific study of religion. - Piedmont, Ralph L., 1958-; Village, Andrew. (Research in the Social Scientific Study of Religion, 2013)
RSSSR continues to offer a place for the publication of theoretical and empirical papers related to the broad area of how the social sciences understand religion. Two papers in the general section add important contributions to the fields of faith development and spirituality. The use of special sections has enabled particular topics to be dealt with in detail and shows how information that is gathered incrementally can help make great advances in a field. Spirituality, alongside religion, features as the key independent variable in many of the nine papers of the special section in this volume. Social scientific approaches have sought to show links between the experiences of health, well-being or disease, and individual differences in religiosity and/or spirituality.